Living with difference: Refugee education and school segregation processes in Greece. (November 2019) - Vergou, Pinelopi
Global challenges and recent changes in conflict areas in the Middle East, Asia and Africa are reasons for the contemporary forced migration into European countries, which have become places of destination or transit posts for a great number of refugees. Cities have become the focus of the socio-spatial debate, as the main units for receiving refugees, either in state camps or in social housing in city centres. In this article, the focus is on the social-spatial configuration of refugee accommodation in local communities and the way these formations generate urban and school segregation. We argue that the placement of urban refugees in large, camp-like structures with low housing standards, mainly in areas outside cities or in rural areas, provides ground not only for social exclusion and 'territorial stigmatisation' but also for de facto school segregation. Furthermore, the attempts to house refugees in small cities, through United Nations and NGO-supplied houses, may also raise concerns about the way dispersal policies are implemented, with the distribution of refugee children in specific schools as a result of territorial social-spatial segregation. In both cases, the school segregation of refugees is connected not only with the implications of immigration and education policies but also with the social practices of local communities and the social-spatial characteristics that determine school education. The empirical material of this study is based on information on the socio-economic profiles of neighbourhoods at the census tract level and on qualitative research, through in-depth semi-structured interviews in two different cities in Greece.